Well-Posedness and General Decay for Nonlinear Damped Porous Thermoelastic System with Second Sound and Distributed Delay Terms - Ouchenane, Djamel; Zennir, Khaled; Guidad, Derradji (Journal of Applied Nonlinear Dynamics, 2026)
As a continuity to the study by M. M. Al-Gharabli et al. in [1], we consider a one-dimensional porous thermoelastic system with second sound, distributed delay term and nonlinear feedback. We show the well-posedness, using the semigroup theory, and establish an explicit and general decay rate result, using some properties of convex functions and the multiplier method. Our result is obtained under suitable assumption on delay without imposing any restrictive growth assumption on the damping term.